An Outcomes Analysis of 2142 Breast Reduction Procedures. Issue 3 (March 2015) - Manahan, Michele Ann; Buretta, Kate J.; Chang, David; Mithani, Suhail K.; Mallalieu, Jesse; Shermak, Michele A.
Abstract : Background: Breast reduction alleviates macromastia symptoms and facilitates symmetrical breast reconstruction after cancer treatment. We investigated a large series of consecutive breast reductions to study important factors that impact outcomes. Methods: An institutional review board–approved, retrospective review of all breast reductions from 1999 to 2009 in a single institution was performed using the medical record for demographics, medical history, physical examination, intraoperative data, and postoperative complications. Multivariate statistical analysis was performed using Stata 1.0. P ⩽ 0.05 defined significance. Results: Seventeen surgeons performed 2152 consecutive breast reductions on 1148 patients using inferior pedicle/Wise pattern (56.4%), medial pedicle/Wise pattern (16.8%), superior pedicle/nipple graft/Wise pattern (15.1%), superior pedicle/vertical pattern (11.6%), and liposuction (0.1%) techniques. Complications included discernible scars (14.5%), nonsurgical wounds (13.5%), fat necrosis (8.2%), infection (7.3%), wounds requiring negative pressure wound therapy or reoperation (1.4%), and seroma (1.2%). Reoperation rates were 6.7% for scars, 1.4% for fat necrosis, and 1% for wounds. Body mass index greater than or equal to 35 kg/m 2 increased risk of infections [odds ratio (OR), 2.3, P = 0.000], seromas (OR, 2.9, P = 0.03), fat necrosis (OR, 2.0, P = 0.002), and minor wounds (OR, 1.7, P = 0.001). Cardiac disease increased reoperation for scar (OR, 3.0, P = 0.04) and fat necrosis (OR, 5.3, P = 0.03). Tobacco use increased infection rate (OR, 2.1, P = 0.008). Secondary surgery increased seromas (OR, 12.0, P = 0.001). Previous hysterectomy/oophorectomy increased risk of wound reoperations (OR, 3.4, P = 0.02), and exogenous hormone supplementation trended toward decreasing infections (OR, 0.5, P = 0.08). χ 2 analysis revealed 7.8% infection risk without exogenous hormone versus 3.8% risk with hormone supplementation ( P = 0.02). Conclusions: Morbid obesity, tobacco, cardiac history, and secondary surgery negatively impacted breast reduction outcomes. Hormonal status impacted reoperations and infections.